Decoding Consumer Perceptions Toward Green Financial Products Using Analytical Hierarchy Process - Pal, Abhinav; Singh, Vikrant Vikram; Tiwari, Chandan Kumar; Bhat, Mohd Abass (Indian Journal of Marketing, 2025)
Purpose : This research used the analytic hierarchy process (AHP) to investigate the key factors influencing consumers to purchase green financial products. Methodology : As a mixed-method study, qualitative expert opinions were combined to select variables with quantitative AHP analysis of the weight of these factors. For the AHP process, six to eight panel experts on sustainable finance, green advertising, and consumer behavior were selected. Findings : The analysis results depicted environmental impact as the most predominant motivator for the consumer, placing trust in green financial products next in order. Awareness driven by cost-effectiveness became less influential, while perceived risk ranked the lowest. In contrast, these results described an increasing confidence on behalf of consumers in the stability and safety of green financial markets. Implications : Basically, the study concluded that the green attributes of financial products should be brought to light, but equally, efforts should be made to increase consumer trust concerning compliance and transparency. Originality : Further, the study introduced a new evaluation parameter for applying AHP in sustainable finance research. Overall, the findings indicated practical implications for eliciting consumer preference and designing strategies to promote green financial products effectively.